Overview: Chronic Pain and Cannabis-Based Medicines - Karst, Matthias (Pharmacopsychiatry, 2024)
Chronic pain is primarily conceptualized as a disease in its own right when it is associated with emotional distress and functional impairment. Pathophysiologically, dysfunction of the cortico-mesolimbic connectome is of major importance, with overlapping signals in the nociceptive and stress systems. The endocannabinoid system plays an important role in the central processing of nociceptive signals and regulates the central stress response. Clinically, there is moderate evidence that cannabis-based medicines (CBM) can contribute to a significant reduction in pain, especially the associated pain affect, and improvement in physical function and sleep quality in a proportion of patients with chronic pain. The analgesic effect appears to be largely independent of the cause of pain. In this context, CBM preferentially regulates stress-associated pain processing.
Keywords: cannabis-based medicines; chronic pain; chronic stress; central sensitization; nociplastic pain